Is there a need for a universal benefit–risk assessment framework for medicines? Regulatory and industry perspectives1. (5th June 2013) - Leong, James; McAuslane, Neil; Walker, Stuart; Salek, Sam
ABSTRACT Purpose To explore the current status and need for a universal benefit–risk framework for medicines in regulatory agencies and pharmaceutical companies. Methods A questionnaire was developed and sent to 14 mature regulatory agencies and 24 major companies. The data were analysed using descriptive statistics, for a minority of questions preceded by manual grouping of the responses. Results Overall response rate was 82%, and study participants included key decision makers from agencies and companies. None used a fully quantitative system, most companies preferring a qualitative method. The major reasons for this group not using semi‐quantitative or quantitative systems were lack of a universal and scientifically validated framework. The main advantages of a benefit–risk framework were that it provided a systematic standardised approach to decision‐making and that it acted as a tool to enhance quality of communication. It was also reported that a framework should be of value to both agencies and companies throughout the life cycle of a product. They believed that it is possible to develop an overarching benefit–risk framework that should involve relevant stakeholders in the development, validation and application of a universal framework. The entire cohort indicated common barriers to implementing a framework were resource limitations, a lack of knowledge and a scientifically validated and acceptable framework. Conclusions Stakeholders prefer a semi‐quantitative, overarching framework that incorporates a toolbox of different methodologies. A coordinating committee of relevant stakeholders should be formed to guide its development and implementation. Through engaging the stakeholders, these outcomes confirm sentiments and need for developing a universal benefit–risk assessment framework. Copyright © 2013 John Wiley & Sons, Ltd.